The effects of calcium-to-phosphorus ratio on the densification and mechanical properties of hydroxyapatite ceramic - Tan, C.Y.; Ramesh, S.; Teh, Y.C.; Tan, Y.M.; Yap, B.K. (John Wiley & Sons, 2015)
In this work, hydroxyapatite (HA) powders were synthesized using calcium hydroxide Ca(OH)(2) and orthophosphoric acid H3PO4 via wet chemical precipitation method in aqueous medium. Calcium-to-phosphorus (Ca/P) ratio was set to 1.57, 1.67, 1.87 that yield calcium-deficient HA, stoichiometric HA, and calcium-rich HA, respectively. These synthesized HA powders (having different Ca/P ratio) were characterized in terms of particle size and microstructural examination. Then, the densification and mechanical properties of the calcium-deficient HA, stoichiometric HA, and calcium-rich HA were evaluated from 1000 to 1350 degrees C. Experimental results have shown that no decomposition of hydroxyapatite phase was observed for stoichiometric HA (Ca/P = 1.67) and calcium-deficient HA (Ca/P = 1.57) despite sintered at high temperature of 1300 degrees C. However, calcium oxide (CaO) was detected for calcium-rich HA (Ca/P = 1.87) when samples sintered at the same temperature. The study revealed that the highest mechanical properties were found in stoichiometric HA samples sintered at 1100-1150 degrees C, having relative density of similar to 99.8, Young's modulus of similar to 120 GPa, Vickers hardness of similar to 7.23 GPa, and fracture toughness of similar to 1.22 MPam(1/2)